KEWAJIBAN MEMFASILITASI PEMBANGUNAN KEBUN MASYARAKAT OLEH PERUSAHAAN PERKEBUNAN KELAPA SAWIT PASCA BERLAKUNYA UNDANG-UNDANG CIPTA KERJA - Shevy, Muhammad (Jurnal De Lege Ferenda Trisakti, 2024)
After the enactment of Law No. 11 of 2020 concerning Job Creation as amended through Government Regulation in Lieu of Law No. 2 of 2022 which was enacted through Law No. 6 of 2023, it has been followed up by the issuance of Government Regulation No. 26 of 2021 concerning the Implementation of the Agriculture Sector and Minister of Agriculture Regulation No. 18 of 2021 concerning Facilitation of Community Plantation Development, the regulation of the obligation to facilitate the development of community plantations provides an option for plantation companies and surrounding communities to carry out partnerships in other forms, but in fact most of the community still understand that plantation companies have the obligation to develop plasma plantations at least 20% of the HGU obtained by the plantation companies. The purpose of this study is to provide an overview of the history of the obligation of developing community plantations (plasma plantations) in Indonesia, regulate the provisions of these partnership obligations whether in line with land regulations, analyze and examine the factors causing the emergence of demands for the development of community plantations or social conflicts between the community and plantation companies, the obligation to facilitate the development of community plantations in other forms of partnership after the enactment of the Job Creation Law. The results of this study to provide an overview of whether the changes in these provisions provide benefits to the community and plantation companies, a sense of justice and improve the economy of the community, legal certainty for plantation companies in order to provide a safe and smooth investment climate. but in practice there is still a gap between expectations (das sollen) and reality (das sein).